ANALISIS KESTABILAN MODIFIKASI MODEL SEIQR PENYEBARAN SARS-COV-2 DENGAN ADANYA MOBILITAS INTERNASIONAL DI INDONESIA - Br Purba, Rohna Lensa; Sinaga, Lasker P (LPPM Universitas Bina Bangsa, 2024)
Coronavirus Disease (COVID-19) is a virus caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Since January 2020, COVID-19 was declared a pandemic by WHO, various countries throughout the world have made efforts to prevent the entry of the COVID-19 outbreak into their respective countries, including Indonesia, by limiting mobility. This research aims to develop a modified SEIQR model for the spread of SARS-CoV-2 in Indonesia by considering international mobility and analyzing the stability of the model. Numerical simulations were also carried out to see the stability results of the SEIQR modification model using suspect data before/after vaccination. The results of this research show that the modified model has two critical points, namely disease-free and disease-endemic critical points, both points are stable when the parameter inequality conditions based on the Routh-Hurwitz criteria are met. Numerical simulations show that the process of suspected infection before vaccination is slower than individual infection after vaccination. From the results of this research, it is concluded that efforts to limit international mobility in Indonesia can reduce the number of new individuals exposed to and infected with COVID-19 in Indonesia.